Peningkatan Pemahaman Teknologi Internet Sehat Bagi Siswa Sekolah Dasar - Anisah, Siti; Suwaebatul Aslamiyah (LPPM POLITEKNIK LP3I, 2024)
Community Service (PKM) is one form of the Tridharma of Higher Education. This PKM is proposed to carry out socialization and educational activities at Madrasah Ibtidaiyah Budi Mulya in West Pademangan, North Jakarta City. This activity is proposed to educate elementary school students about healthy internet use. This activity is carried out by observing that internet use in the student environment is very difficult to inhibit or limit. In today's modern era, internet use can not only be done via computer devices, but can also be accessed via smart devices or smartphones. So it is increasingly difficult to control children's use of the internet. However, many internet users are not aware of the dangers of negative impacts from the internet. Therefore, it is necessary to increase vigilance and awareness of the dangers of the negative impacts of the internet which are unconsciously carried out by internet users, especially students in elementary schools. Based on these problems, the idea of socializing and educating healthy internet use for elementary school students could be one of disseminating knowledge and training regarding healthy internet use for education and for students.